PERAN ORANG TUA DALAM PENANAMAN NILAI AQIDAH PADA ANAK DI KELURAHAN BANDAR SELAMAT KECAMATAN MEDAN TEMBUNG - Maraimbang Maraimbang; Abrar M. Dawud Faza; Rahma Yanti Daulay (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2020)
The role of parents who have a good level of understanding of religion, can guide the guidance of aqidah and worship to their children well, the level of obedience of children is very good, mothers have a more dominant role in guiding and directing children in the field of aqidah. has been able to form the personality of a devout child in carrying out worship. Parents who lack religious understanding tend to care less about their children to study religion well. Qualitative methods and conducting research in field research using data collection techniques in this study using the method of free interviews and observations and documentation methods in the village of Bandar Selamat, Medan Tembung District. Results in the Study of the Role of Parents in Guiding Their Children to Instill Aqeedah Values and become the basis and determinant for the survival of the Child in the future because this problem becomes a very important thing to be studied and examined its presence in the community. Because not all parents are able to instill the value of Aqeedah to their children, especially for parents who lack adequate religious knowledge. For parents instilling the value of aqi ̅dah in children from an early age is the first and foremost thing. Instilling the value of aqidah is a must that must not be abandoned. Because aqi ̅dah is a pillar that underlies one's Islam. Aqi ̅dah value or faith in early childhood is a basic foundation for life according to nature, because humans have the nature and tendency to experience and believe in the existence of God.Keywords: Parents, Planting, Aqeedah Values, Childre.